Ser326Cys polymorphism of hOGG1 gene in postmenopausal breast cancer women from the Lodz region of Poland - Sobczuk, Anna; Smolarz, Beata; Romanowicz-Makowska, Hanna; Zadrożny, Marek; Baszczyński, Jakub; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2009)
Reduced DNA repair capacity can render a high risk of developing many types of cancer including breast cancer. Polymorphisms in DNA repair genes may contribute the genetic instability and carcinogenesis. In the present work the distribution of genotypes and frequency of alleles of the Ser326Cys polymorphism of the hOGG1 gene in postmenopausal breast cancer women were analysed. Blood samples were obtained from 100 women with breast cancer and control (n = 106). The polymorphisms were determined by PCR-RFLP methods. No association between Ser326Cys polymorphism of hOGG1 and breast cancer risk was observed. The distribution of the genotypes of the Ser326Cys polymorphism in both controls and patients did not differ significantly (p > 0.05) from those predicted by the Hardy-Weinberg distribution. There were no significant differences (p > 0.05) in genotype distributions and allele frequencies between subgroups assigned to histological stage. The results suggest that the Ser326Cys polymorphism of the hOGG1 gene may not be linked with appearance and development of breast cancer in women from the Lodz region of Poland.